Sensitivity of the Atlantic Meridional Overturning Circulation to Model Resolution in CMIP6 HighResMIP Simulations and Implications for Future Changes. (8th August 2020) - Roberts, Malcolm J.; Jackson, Laura C.; Roberts, Christopher D.; Meccia, Virna; Docquier, David; Koenigk, Torben; Ortega, Pablo; Moreno‐Chamarro, Eduardo; Bellucci, Alessio; Coward, Andrew; Drijfhout, Sybren; Exarchou, Eleftheria; et al.
Abstract: A multimodel, multiresolution ensemble using Coupled Model Intercomparison Project Phase 6 (CMIP6) High Resolution Model Intercomparison Project (HighResMIP) coupled experiments is used to assess the performance of key aspects of the North Atlantic circulation. The Atlantic Meridional Overturning Circulation (AMOC), and related heat transport, tends to become stronger as ocean model resolution is enhanced, better agreeing with observations at 26.5°N. However, for most models the circulation remains too shallow compared to observations and has a smaller temperature contrast between the northward and southward limbs of the AMOC. These biases cause the northward heat transport to be systematically too low for a given overturning strength. The higher‐resolution models also tend to have too much deep mixing in the subpolar gyre. In the period 2015–2050 the overturning circulation tends to decline more rapidly in the higher‐resolution models, which is related to both the mean state and to the subpolar gyre contribution to deep water formation. The main part of the decline comes from the Florida Current component of the circulation. Such large declines in AMOC are not seen in the models with resolutions more typically used for climate studies, suggesting an enhanced risk for Northern Hemisphere climate change. However, only a small number of different ocean models are included in the study. Plain Language Summary: The ocean circulation in the North Atlantic is important for Northern Hemisphere climate, and hence, it is important to assess the risk of changes caused by climate change. In this work we use seven different global coupled climate models to simulate the period 1950–2050, using different horizontal grid spacings of the ocean (and atmosphere) models. We find that, when assessed against observations at 26.5°N in the Atlantic, the higher‐resolution models tend to perform better, though this is not so obviously the case at higher latitudes. In the future projections to 2050, the higher‐resolution models typically have a larger reduction in their ocean circulation compared to the lower‐resolution models, with potential implications for climate risk and impacts. Key Points: The Atlantic Meridional Overturning Circulation and northward heat transport typically increase in strength at higher horizontal model resolution The Atlantic Meridional Overturning Circulation in most of the higher‐resolution models declines more quickly in the future projections The results suggest that to fully assess the risk of changes to Atlantic Ocean circulation requires use of higher‐resolution models